Modeling the role of emotion regulation and critical thinking in immunity in higher education - Li, Meilan; Heydarnejad, Tahereh; Azizi, Zeinab; Rezaei Gashti, Zeynab (Frontiers in Psychology, 2022)
It is deemed that the effectiveness of teachers is highly entangled with psycho-emotional constructs, such as critical thinking (CT), emotion regulation (ER), and immunity. Despite the potential roles of CR, ER, and immunity, their possible relationships have remained unexplored in higher education context of Iran. To fill in this lacuna, this study explored the potential role of CT and ER in university teachers’ immunity in the Iranian higher education context. For this purpose, a total of 293 English university teachers were selected using a convenience sampling method. They were invited to fill out the Watson–Glaser Critical Thinking Appraisal-Form, Language Teacher Emotion Regulation Inventory, and Language Teacher Immunity Instrument. The findings of path analysis indicated that the university teachers with higher CT were more productively immunized. Moreover, the results revealed that ER could predict the university teachers’ immunity. The findings of the study lead to this implication that higher order thinking skills, emotion regulatory strategies, and immune enhancement should be incorporated into educational programs of higher education.